Optimization of polymers for organic solar cells: Effects of alkyl, fluorinated and thiophenated chains - Kalsum Ahmad Mustamin; Mohd Sani Sarjadi; Shaheen M. Sarkar; Sandeep Kumar; Md Lutfor Rahman (Wiley-VCH GmbH, Weinheim, 2025)
This paper explores optimization strategies for polymeric materials in organic solar cells (OSCs) with the focus on varying alkyl side chain, addition of fluorine atom, and thiophenated derivatives onto polymer. As such, it outlines the significance of renewable energy sources and the potential of photovoltaic technologies, particularly organic photovoltaics (OPVs). Objectives include factors affecting power conversion efficiency (PCE), open-circuit voltage (Voc), aggregation tendencies, and optoelectronic properties in OPVs. The scope encompasses the impact of alkyl as well as the comparison between fluorinated and chlorinated polymers and the role of thiophene units to obtain an efficient organic solar cell. The review examines how alkyl chain structures influence thin film morphology, packing, and device performance, comparing linear and branched configurations. It also explores the role of halogenated polymers in modifying electronic properties and stability, focusing on the comparative performance between fluorinated and chlorinated polymers. The importance of thiophene units in polymer design for OPVs is discussed, along with performance comparisons based on different architectures. The paper summarizes key findings regarding the impact of various side chain modifications for OPVs device performance and outlines future research directions to enhance efficiency, stability, and scalability. It suggests exploring novel material design to further optimize OSCs.